A sheet of paper - Perry, Clara Jeanette (My University, 1898)
Introduction: The three staple articles of manufacture that are most essential to modern civilization, it is said, are food, clothing and paper. If this estimate of the importance of the paper industry is a correct one, then people generally are deplorably ignorant of one of the most familiar as well as most indispensable articles of our civilization. There are few people indeed who know anything of the processes thru which a sheet of paper must go before it is ready for use. Discovery interesting to trace the evolution of writing materials from the light, smooth substances such as some barks or broad leaves anciently used to transmit short and simple messages, to the thin sheets of metal, ivory or leather, painted cloths, stones and bricks. Then as the wants of communities become more complex, the population increased, and materials for records as well as for messages were necessary, inscribed leaves strung upon threads for preservation, the bark of trees made pliant enough to be rolled, or thin strips of wood covered with was, were all substituted for the more primitive materials. The industry developed little by little until parchment and papyrus used by the Greeks, the Persians and the Egyptians were superseded by the Chinese invention – Paper.
Citation: Perry, Clara Jeanette. A sheet of paper. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Civilization; Paper; Evolution; Greek; Egyptians; Theses; Manuscripts (documents)